تأثير معالجة البذور ومياه الري بتقنية البلازما على خصائص انبات ونمو نبات القمح - دراسة حالة صنفي - مسعودي محمد (سوسة – تونس, 2024)
تستهدف تقنية البلازما تعقيم البذور وتحسين ظروف تخزينها. كذلك يُعترف بهذه الطريقة كأحد الأساليب المستخدمة في معالجة مياه الري المالحة، بالإضافة إلى تقنيات مثل التمغنط. ونتيجة لذلك، فإن تقنية البلازما قادرة على تحسين عمليات الإنبات وتطوير الجذور ونمو النبات بشكل عام. تقوم هذه الدراسة بتقييم تأثير تقنية البلازما على خصائص الإنبات والنمو لصنفين من نبات القمح: Ble tendre HD 1220 وBle dun Amar 06. تم تصميم التجربة لتقييم تأثير معالجة البذور ومياه الري بتقنية البلازما، حيث تم اختيار 6 معاملات لكل صنف، ممثلة في ماء عادي بدور عادية 0T، وماء معالج بدور عادية 1T، وماء عادي بدور رطبة 2T، وماء معالج بدور رطبة 3T، وماء عادي بدور جافة 4T، وماء معالج بدور جافة 5T، بثلاث تكرارات لكل معاملة. تم تقييم الخصائص الفيزيولوجية والمورفولوجية للنباتات، بالإضافة إلى تحليل تشريح الأوراق والجذور والساق. أظهرت النتائج تأثيرًا واضحًا للبلازما على خصائص النمو الخضري والتشريحية والفيزيولوجية خلال مراحل النمو والانبات للصنفين. ولوحظت زيادة في معدلات النمو الخضري مثل سمك الساق، ارتفاع النبات، عدد الأوراق، وعدد الأفرع، بالإضافة إلى تحسين قياسات كيميائية مثل تقدير كمية الكلوروفيل الكلي وكمية السكريات الذائبة. Abstract: Plasma technology targets the sterilization of seeds and the enhancement of their storage conditions. This method is recognized as one of the approaches employed in treating saline irrigation water, in addition to techniques like magnetization. Consequently, plasma technology has the potential to improve germination, root development, and overall plant growth processes. This research assesses the effects of plasma technology on the germination and growth attributes of two wheat varieties, Ble tendre HD 1220 and Ble dun Amar 06. The experiment was designed to assess the effect of plasma treatment on seeds and irrigation water, with 6 treatments selected for each variety, represented by normal water in a normal cycle (0T), treated water in a normal cycle (1T), normal water in a wet cycle (2T), treated water in a wet cycle (3T), normal water in a dry cycle (4T), and treated water in a dry cycle (5T), with three repetitions for each treatment. Physiological and morphological characteristics of the plants were evaluated, in addition to analyzing leaf, root, and stem anatomy. The results clearly showed the impact of plasma technology on vegetative growth, anatomical, and physiological characteristics during the growth and germination stages of both varieties. An increase in vegetative growth rates such as stem thickness, plant height, leaf count, and branch count was observed, along with improved chemical measurements such as total chlorophyll estimation and soluble sugar content
Ble tendre HD 1220 وBle dun Amar 06
Intervention
Keywords: مغنطة المياه; خصائص محصول القمح; Water magnetization; wheat crop characteristics